2020
DOI: 10.26633/rpsp.2020.53
|View full text |Cite
|
Sign up to set email alerts
|

Comparing South Korea and Italy’s healthcare systems and initiatives to combat COVID-19

Abstract: Italy and South Korea have two distinctly different healthcare systems, causing them to respond to public health crises such as the COVID-19 pandemic in markedly different ways. Differences exist in medical education for both countries, allowing South Korean medical graduates to have a more holistic education in comparison to their Italian counterparts, who specialize in medical education earlier on. Additionally, there are fewer South Korean physicians per 1000 people in South Korea compared to Italian physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
10

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 10 publications
(17 reference statements)
1
13
0
10
Order By: Relevance
“…[315][316][317] The countries (Taiwan, Hong Kong, South Korea, and Japan) heavily invested in PHC after SARS and MERS have managed much better than others. 310,[318][319][320][321][322][323][324][325][326][327] Taiwan took lessons from SARS on fighting back against the viral epidemic. 328,329 It has been reported that Taiwan successfully deferred and controlled community transmission of COVID-19 because the country experienced, learned, and utilized how to manage the viral epidemic of 2003.…”
Section: Primary Health Care In the Management Of The Global Pandemicmentioning
confidence: 99%
“…[315][316][317] The countries (Taiwan, Hong Kong, South Korea, and Japan) heavily invested in PHC after SARS and MERS have managed much better than others. 310,[318][319][320][321][322][323][324][325][326][327] Taiwan took lessons from SARS on fighting back against the viral epidemic. 328,329 It has been reported that Taiwan successfully deferred and controlled community transmission of COVID-19 because the country experienced, learned, and utilized how to manage the viral epidemic of 2003.…”
Section: Primary Health Care In the Management Of The Global Pandemicmentioning
confidence: 99%
“…Dessa forma entende-se a importância da educação da sociedade. Por outro lado, a Itália, que foi um dos países que mais sofreu com a pandemia, deveuse em parte à natureza reativa das medidas de saúde pública no país em comparação com a resposta pró-ativa da Coreia do Sul (Palaniappan, et al, 2020).…”
Section: Resultsunclassified
“…This is due to the fact that European countries have age structures biased to higher age classes. This is likely one of the reasons why European countries have had high death tolls, and why mortality may be lower in other continents [17,28], although many other additional reasons have been suggested [29][30][31]. is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Resultsmentioning
confidence: 99%